Hypomagnesemia in persons with type 1 diabetes: associations with clinical parameters and oxidative stress - Dijk, Peter R. van; Waanders, F.; Qiu, Jiedong; Boer, Hannah H. R. de; Goor, H. van; Bilo, H. J. G. (Therapeutic advances in endocrinology and metabolism, 2020)
Background: Among persons with type 1 diabetes mellitus (T1DM) low concentrations of magnesium have been reported. Previous (small) studies also suggested a relation of hypomagnesemia with (poor) glycaemic control and complications. We aimed to investigate the magnitude of hypomagnesemia and the associations between magnesium with parameters of routine T1DM care in a population of unselected outpatients. - Methods: As part of a prospective cohort study, initially designed to measure quality of life and oxidative stress, data from 207 patients with a mean age of 45 [standard deviation (SD) 12] years, 58% male, diabetes duration 22 [interquartile range (IQR) 16, 31] years and glycated haemoglobin (HbA1c) of 60 (SD 11) mmol/mol [7.6 (SD 1.0)%] were examined. Hypomagnesemia was defined as a concentration below <0.7 mmol/l. - Results: Mean magnesium concentration was 0.78 (SD 0.05) mmol/l. A deficiency was present in 4.3% of participants. Among these persons, mean concentration was 0.66 (SD 0.03) mmol/l. There was no correlation between magnesium and HbA1c at baseline (r = -0.014, p = 0.843). In multivariable analysis, free thiols (reflecting the degree of oxidative stress) were significantly and negatively associated with magnesium concentrations. - Conclusion: In this cohort of T1DM outpatients, the presence of hypomagnesemia was infrequent and, if present, relative mild. Magnesium was not associated with glycaemic control nor with presence of micro- and macrovascular complications. Although these results need confirmation, in particular the negative association of magnesium with free thiols, this suggests that hypomagnesemia is not a relevant topic in routine care for people with T1DM.